Wave and Tidal Energy: A Patent Landscape Study - Mohamadreza Pazhouhan; Amin Karimi Mazraeshahi; Mohammad Jahanbakht; Kourosh Rezanejad; Mohammad Hossein Rohban (Journal of Marine Science and Engineering)
Wave and tidal energy, recognized as vital renewable resources, harness the ocean’s kinetic and potential power. This study aims to provide an in-depth patent analysis of the technological landscape within these sectors. We applied a dual approach: first, a descriptive analysis was conducted to explore patent publication trends, technology lifecycle stages, patent activity by country, top assignees, and IPC classifications. Our analysis provided a detailed overview of the sector’s growth and the key players involved. Second, we utilized topic modeling, specifically BERTopic enhanced with large language models, to identify and fine-tune key technological themes within the patent data. In this study, we identified seven distinct clusters each for wave and tidal energy using this approach. This method led to a novel categorization of the patents, revealing latent themes within the patent data. Although our categorization differs from traditional methods, it provides deeper insights into the thematic focus of the patents, highlighting emerging trends and areas of innovation within wave and tidal energy technologies to better exploit and optimize ocean energy conversion infrastructure.